Foveolar muller cells of the pied flycatcher: morphology and distribution of intermediate filaments regarding cell transparency - Zueva, Lidia (2017)
Specialized intermediate filaments (IFs) have critical importance for the clearness and uncommon transparency of vertebrate lens fiber cells, although the physical mechanisms involved are poorly understood. Recently, an unusual low-scattering light transport was also described in retinal Muller cells. Exploring the function of IFs in Muller cells, we have studied the morphology and distribution pattern of IFs and other cytoskeletal filaments inside the Muller cell main processes in the foveolar part of the avian (pied flycatcher) retina. We found that some IFs surrounded by globular nanoparticles (that we suggest are crystallines) are present in almost every part of the Muller cells that span the retina, including the microvilli. Unlike IFs implicated in the mechanical architecture of the cell, these IFs are not connected to any specific cellular membranes. Instead, they are organized into bundles, passing inside the cell from the endfeet to the photoreceptor, following the geometry of the processes, and repeatedly circumventing numerous obstacles. We believe that the presently reported data effectively confirm that the model of nanooptical channels built of the IFs may provide a viable explanation of Muller cell transparency.